Research Progress on the Mechanism of Mitochondrial Autophagy in Cerebral Stroke - Lei, Li; Yang, Shuaifeng; Lu, Xiaoyang; Zhang, Yongfa; Li, Tao (Frontiers in Aging Neuroscience, 2021)
Mitochondrial autophagy is an early defense and protection process that selectively clears dysfunctional or excessive mitochondria through autophagy mechanism to maintain intracellular homeostasis. Mitochondrial dysfunction during cerebral stroke involves metabolic disbalance, oxidative stress, apoptosis, endoplasmic reticulum stress and abnormal mitochondrial autophagy. This paper reviews the research progress on the mechanism of mitochondrial autophagy in ischemic stroke. In order to provide a theoretical basis for further research on mitochondrial autophagy and the treatment of ischemic stroke.